Impact of laparoscopic radical prostatectomy on clinical T3 prostate cancer: experience of a single centre with long‐term follow‐up. (27th March 2015) - Gözen, Ali S.; Akin, Yigit; Ates, Mutlu; Hruza, Marcel; Rassweiler, Jens
<x xml:space="preserve">Abstract</x> Objective To investigate the oncological safety and effectiveness of laparoscopic radical prostatectomy (LRP) for patients with clinical T3 (cT3) prostate cancer compared with patients with cT1 and cT2 prostate cancer. Patients and Methods In all, 2375 consecutive LRPs were evaluated between 1999 and 2013. Of the 1751 patients enrolled with complete follow‐up data (>24 months), patients were divided into three groups according to clinical stage of prostate cancer using Tumour‐Node‐Metastasis (TNM) classification. Group 1 consisted of patients with cT1 stage prostate cancer, group 2 those with cT2, and group 3 those with cT3. Demographic, postoperative, and long‐term data of patients were recorded and statistical analyses were performed. Results The mean (sd) age was 63.6 (6.2) years. The mean (sd) follow‐up was 104 (28.4) months. There were 417 patients in group 1, 842 patients in group 2, and 492 patients in group 3. The mean prostate‐specific antigen level, biopsy Gleason score, tumour volume, body mass index, and age, were all higher in group 3 (P < 0.001). Nerve‐sparing techniques were used more in group 1 than in the other groups (P < 0.001). Extracapsular extension, seminal vesicle invasion, Gleason score, positive surgical margin (PSM), and rate of adjuvant hormone and radiotherapies were highest in group 3. However, urinary continence was similar in all groups. Group 1 contained the most patients with an erection sufficient for intercourse. Group 1 had the best cancer‐specific survival rate, whereas overall survival (OS) rates and complications were similar in all groups. Conclusion LRP seems effective and safe for patients with cT3 prostate cancer with similar OS rates as for those with cT1 and cT2; however, additional therapies may have contributed to these rates. LRP can be considered for the treatment of patients with cT3 prostate cancer.